ETHICAL ASPECTS OF EDUCATIONAL ACTIVITIES: PAST AND PRESENT - Alexey V. Bogachev; Liudmila B. Zakharova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article analyzes the historical experience and current approaches of ethics education. The term "ethics" was first used by Aristotle. Philosopher put ethics between the doctrine of the soul and the state: based on the first, it had to give reasons for the second. Problems of Education devoted a significant part of a larger work of Plato's "Republic". His educational project conscious purpose -the smooth functioning of the ideal state. Today, teachers of high school must first of all take care of them oral education, moral culture of students. The lecture must meet the following main principles: short, consistency, focus, gain efficiency. Activation of the listener's attention is achieved through a number of etiquette practices.